1996
DOI: 10.1093/oxfordjournals.jbchem.a021531
|View full text |Cite
|
Sign up to set email alerts
|

Fine Substrate Specificities of Four Exo-Type Cellulases Produced by Aspergillus niger, Trichoderma reesei, and Irpex lacteus on (1->3),(1->4)- -D-Glucans and Xyloglucan

Abstract: To investigate the fine substrate specificities of four highly purified exo-type cellulases (Exo-A from Aspergillus niger, CBHI and CBHII from Trichoderma reesei, and Ex-1 from Irpex lacteus), water-soluble substrates such as barley glucan, xyloglucan from tamarind (Tamarindus indica L.), and their oligosaccharides were employed. Four exo-type cellulases immediately hydrolyzed 3-O-beta-D-cellotriosylglucose to produce cellobiose and laminaribiose. In contrast, CBHII showed no hydrolytic activity towards 3(2)-O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…In particular, it was reported that Ex 1 had higher hydrolytic activity toward (1 3),(1 4) D glucan than other exo type cellulases. 13) On the other hand, CBH II was found as the inverting enzyme performing the reaction by the single displacement mechanism without transglycosylation. 18) In order to investigate the transglycosylation mechanism of CBH I, the mode of G3 hydrolysis was estimated by using G3H as a substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, it was reported that Ex 1 had higher hydrolytic activity toward (1 3),(1 4) D glucan than other exo type cellulases. 13) On the other hand, CBH II was found as the inverting enzyme performing the reaction by the single displacement mechanism without transglycosylation. 18) In order to investigate the transglycosylation mechanism of CBH I, the mode of G3 hydrolysis was estimated by using G3H as a substrate.…”
Section: Discussionmentioning
confidence: 99%
“…10,11) Ex 1 and Exo A were also purified from Driselase (from I. lacteus, Kyowa Hakko Co., Ltd.) and Sumizyme AC (from A. niger, Shin Nihon Chemical Co., Ltd.), respectively. 12,13) Substrates. Cello oligosaccharides and pNP glycosides used in this experiment were purchased from Seikagaku Kogyo Co., Ltd.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This model, however, is inconsistent with several features of cellulose degradative systems. Thus, biochemical and structural data indicate that GH6 cellobiohydrolases are not, exclusively, exo acting (Amano et al, 1996;Armand et al, 1997;Varrot et al, 1999). Furthermore, some highly active cellulase systems lack a classic pair of cellobiohydrolases that act from the reducing and nonreducing ends of cellulose chains, respectively (Xie et al, 2007;Weiner et al, 2008).…”
Section: Cellulasesmentioning
confidence: 99%
“…5 in Wilson et al, 2006). However, CBHII also binds to the (1→4)-b-oligoglucoside structures in (1→3, 1→4)-b-D-glucan and xyloglucan (Henriksson et al, 1995;Amano et al, 1996). We assumed at 3 and 4 DAP, CBHII was binding to cellulose because (1→3, 1→4)-b-D-glucan is not deposited until after 4 DAP and xyloglucan is absent in the mature grain (Fincher, 1975;Stone, 1981a, 1981b).…”
Section: Xyloglucan Deposition During Cellularization (3-8 Dap)mentioning
confidence: 99%